Long and short-term trends of stream hydrochemistry and high frequency surveys as indicators of the influence of climate change, agricultural practices and internal processes (Aurade agricultural catchment, SW France). (March 2020) - Ponnou-Delaffon, Vivien; Probst, Anne; Payre-Suc, Virginie; Granouillac, Franck; Ferrant, Sylvain; Perrin, Anne-Sophie; Probst, Jean-Luc
Highlights: The 35-years hydrochemical survey indicated an obvious decrease of nitrate. Over 15 years, Ca, HCO3 and strong acid anions decreased while DOC and K increased. Agricultural practices, temperature and discharge were key controlling factors. Continuous probe surveys clearly indicated diel cycles of hydrochemical parameters. The various time scale surveys evidenced a set of hydro-biogeochemical processes. Abstract: The hydrochemical time series of stream water from a cultivated catchment were investigated at different time scales and survey frequencies. A 35-year time series of nitrate concentration and discharge, a 15-year time series of major elements and dissolved organic carbon (DOC) concentrations were analysed from a yearly to a daily/hourly basis during discharge recession after storm event periods, to determine the origin of elements, the time trends and the main controlling factors of the trends. A significant decrease over time of nitrate, base cations and other major anions was observed. These trends were controlled by agricultural practice changes (decrease of N -fertiliser input, grass-band set up) and discharge increase, especially in the last years of the period. On the other hand, K and DOC increased over the 15-year period. This increase might result from both 1) organic matter eroded from the soil surface by runoff during flood events and 2) an increase in mineralisation with increasing temperature. Seasonal variations and nycthemeral cycles indicated either calcite precipitation and nitrification processes and/or evapotranspiration, water and/or vegetation uptake during the day with increasing temperature. This paper highlights that the hydrochemical parameters measured at various time scales and frequencies can be used as powerful indicators of catchment internal processes, and of changes in agricultural management and climate change. Particularly, the multivariate high-resolution survey has shown its ability to evidence very tenuous processes not detectable by discrete sampling. The recent observed changes in hydrology argue for the need to continue the hydrochemical survey over decades.